2017
DOI: 10.1002/2017ef000606
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to flood risk: Results of international paired flood event studies

Abstract: As flood impacts are increasing in large parts of the world, understanding the primary drivers of changes in risk is essential for effective adaptation. To gain more knowledge on the basis of empirical case studies, we analyze eight paired floods, that is, consecutive flood events that occurred in the same region, with the second flood causing significantly lower damage. These success stories of risk reduction were selected across different socioeconomic and hydro‐climatic contexts. The potential of societies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 199 publications
(164 citation statements)
references
References 45 publications
(80 reference statements)
3
148
0
Order By: Relevance
“…In this work, dry periods were evaluated using the SPI at different time scales (3,6,12, and 24 months). While the 3-and 6-month SPI describe droughts that affect plant life and farming, the 12-and 24-month SPI influence the way water supplies and reserves are managed [50,51].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, dry periods were evaluated using the SPI at different time scales (3,6,12, and 24 months). While the 3-and 6-month SPI describe droughts that affect plant life and farming, the 12-and 24-month SPI influence the way water supplies and reserves are managed [50,51].…”
Section: Methodsmentioning
confidence: 99%
“…Since the beginning of the 20th century, the highest concentration of anthropogenic greenhouse gases since the pre-industrial era and an increase in mean global temperatures of about 0.9 • C have been detected [1]. As a consequence, anthropic systems and terrestrial ecosystems are becoming more vulnerable to environmental phenomena and an increase in floods, heat waves, forest fires, and droughts can be expected [2,3]. In particular, the Intergovernmental Panel on Climate Change (IPCC) warned about the possible intensification of droughts in this century, especially in some areas such as the Mediterranean basin [1].…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, the results of recent ABM studies show that societal water-climate systems all have the characteristics of complex systems, marked by time periods of both stability and large dynamics; 81,82 historical data regarding investments in flood protection show little change in the behavior of governments and households after floods that had a small impact, and large investment dynamics in adaptation following large disasters. 83 For instance, recent research into flood-risk trends in the Netherlands shows that, without considering behavioral aspects, future risk is overestimated by a factor of 2. 77 This is confirmed by Wind et al, 84 who observed a 35% decrease in losses for a large flood on the River Meuse in 1995 compared to a similar flood in 1993, which was primarily caused by the adaptive behavior of households.…”
Section: Advances In Risk Assessment and Behavioral Researchmentioning
confidence: 99%
“…Floods are among the most destructive water-related hazards and are mainly responsible for the loss of human lives, infrastructure damages and economic losses [1]. Nowadays, there is a rising global awareness of flood damage mitigation due to the increase in frequency, magnitude, and intensity of flood events [2,3]. In the Mediterranean region, there are many small-medium sized watersheds, which have significant elevation changes (from mountainous areas to plains and even coastal areas).…”
Section: Introductionmentioning
confidence: 99%